Human X chromosome markers and Duchenne muscular dystrophy. - Davies, K E (1985)
Two DNA markers, a random DNA fragment 754 and the cDNA sequence encoding the gene for ornithine transcarbamylase (OTC) have been studied in kindreds segregating for Duchenne muscular dystrophy. 754 and OTC are located close physically to the mutation in the region Xp21 below the breakpoints in two Duchenne females. The genetic distance was found to be approximately 10cM between 754 and DMD (two crossovers in 26 meioses) and to be approximately 10cM between OTC and DMD (two crossovers in 26 meioses). Physical data suggest the order DMD-754-OTC. The frequency of recombination compared to physical distance between these markers and DMD suggests that there may be a hot spot of recombination. The relevance of these observations for the isolation of the DMD mutation and clinical use of these probes is discussed.